Fuzzy Maximal ????-open and Minimal ????-closed Sets via Generalized Fuzzy Topology - A. Swaminathan,; Margret Sheela, (Utilitas Mathematica, 2025)
In this study, we propose the notions of fuzzy maximal ???? -open and fuzzy minimal ???? -closed sets within the framework of generalized topological spaces. We further investigate their fundamental properties and examine their roles in the underlying structure.